2018
DOI: 10.1021/acsomega.7b01958
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Ammonia Gas Sensing Using Mixed-Valent CuCo2O4 Nanoplatelets: Performance Enhancement through Stoichiometry Control

Abstract: We report the sensing properties of an interesting ternary oxide CuCo 2 O 4 (CCO) which comprises two earth-abundant transition elements, both capable of supporting multiple valence states. We have used a synthesis protocol, which renders unique nanoplatelet-type morphology but with a degree of biphasic character (CuO as a secondary phase in addition to the defect-spinel Cu 1– x Co 2 O 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Doping of metal ions in SMONs can increase the number of active sites and defects on the surface of SMON nanocrystals, and thus enhance the amount of oxygen species and increase the adsorbed gas molecules on the sensor's surface. Therefore, the gas sensing performance of the SMONs can be effectively improved by doping of metal ions including Al 3+ , 117,271 Cu 2+ , 272,273 Zn 2+ , 274 Ni 2+ , 275,276 Co 3+ , 277,278 Fe 3+ , 279 Mg 2+ 280 and Sb 5+ . 281 The recent key sensing applications of RT gas sensors using this method are summarized in Table 4.…”
Section: Review Materials Horizonsmentioning
confidence: 99%
“…Doping of metal ions in SMONs can increase the number of active sites and defects on the surface of SMON nanocrystals, and thus enhance the amount of oxygen species and increase the adsorbed gas molecules on the sensor's surface. Therefore, the gas sensing performance of the SMONs can be effectively improved by doping of metal ions including Al 3+ , 117,271 Cu 2+ , 272,273 Zn 2+ , 274 Ni 2+ , 275,276 Co 3+ , 277,278 Fe 3+ , 279 Mg 2+ 280 and Sb 5+ . 281 The recent key sensing applications of RT gas sensors using this method are summarized in Table 4.…”
Section: Review Materials Horizonsmentioning
confidence: 99%
“…A similar effect of humidity on NH 3 has also been observed in the bottom gate graphene FET and metal oxide based chemiresistor sensors. [ 19 ] Close inspection reveals that the recovery time elongates with the increase in humidity. The recovery ratios calculated as ( I gas − I end )/( I gas − I air ) are observed to decrease (increase) with the humidity (area coverage) for all the sensors.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the Zn 2 SnO 4 -SnO 2 composite film showed a high SR to NH 3 gas compared with other composite thin filmbased NH 3 sensors reported in the literature (Table 4). [16,[44][45][46][47][48][49] This may be due to the presence of more number of oxygen ions on the surface of the film. [26] The high SR of the film to NH 3 made it as a hopeful material for the NH 3 gas sensor at room-temperature working condition.…”
Section: Sensor Responsementioning
confidence: 99%
“…The requirement of room-temperature NH 3 sensor directed the researchers toward the development of sensing material to be operated at room temperature. [16] Due to this a lot of room-temperature NH 3 sensors are developed recently. [3,[17][18][19][20] Despite that, the reports on room-temperature NH 3 sensors based on ZnO-SnO 2 composite material are limited.…”
mentioning
confidence: 99%